2000
DOI: 10.1111/j.1745-4565.2000.tb00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Apple Growing, Harvesting, and Cider Manufacturing Practices in Wisconsin: Implications for Safety

Abstract: To evaluate the safety of current apple growing, harvesting and cider manufacturing practices in Wisconsin, cider manufacturers were contacted in a three‐phase survey. Results revealed that seasonal, small‐scale production was characteristic of the industry. Most cider mills produced less than 5,000 gal/year; only 6% produced more than 20,000 gal/year. Most cider makers used only tree picked apples (86%), inspected apples before washing (94%), washed (93%) and brushed (87%) apples, but only 16% of mills saniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Freeze–thaw treatment is a common method for extending the shelf life of apple cider (Uljas and Ingham 2000). Many researchers have reported that freezing has considerable lethality against many microorganisms, including E. coli , Listeria monocytogenes , Salmonella Typhimurium, Vibrio parahaemolyticus , and Vibrio vulnificus in microbial growth media and selected food systems (Cressy and others 2003; Elhanafi and others 2004; Ternent and others 2004; Wong and others 2004; Ingham and others 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Freeze–thaw treatment is a common method for extending the shelf life of apple cider (Uljas and Ingham 2000). Many researchers have reported that freezing has considerable lethality against many microorganisms, including E. coli , Listeria monocytogenes , Salmonella Typhimurium, Vibrio parahaemolyticus , and Vibrio vulnificus in microbial growth media and selected food systems (Cressy and others 2003; Elhanafi and others 2004; Ternent and others 2004; Wong and others 2004; Ingham and others 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Injury and cell death are enhanced as this storage temperature increases (42,43,47). Many cider makers also freeze their cider for later sale (44), which further stresses cells and may result in cell death (34). Although individual studies have demonstrated the potential lethality of these steps, a systematic approach to describe microbial responses to such treatments and their combinations is needed for use in developing effective pathogen control strategies for cider.…”
mentioning
confidence: 99%
“…In a noncontinuous process, commonly used by small cider processors, a sufficient amount of cider must be first collected before proceeding to the next step. Cider may, therefore, sit in the holding tank for a time ranging from a few hours to overnight (44), a period during which cells may become injured. Injury and cell death are enhanced as this storage temperature increases (42,43,47).…”
mentioning
confidence: 99%
“…Other forms of contamination by pathogens in this product, including irrigation water, lack of hygiene practices in collection and disinfection of transport boxes, as well as the period and conditions of storage, have all been documented (Buchanan et al . ; Uljas and Ingham ; Garcia et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…The fermentation process itself is an effective means of reducing pathogen load and patulin contamination. However, many microorganisms (yeast and bacteria), can still affect cider quality and stability, so Standard Sanitary Operating Procedures (SSOPs) and product stabilization should still be addressed in the production plan (Uljas and Ingham ).…”
Section: Introductionmentioning
confidence: 99%